(untitled) (Emancipação, 2024)
This article is part of studies carried out in a research project whose objective is to identify how the debate on the fundamentals of Social Work is carried out in Social Work qualification in Paraná. To this end, we carried out qualitative research through bibliographic and documentary reviews of the Course’s Pedagogical Projects. At this time, the research was limited to approach aspects of the professional profile and mandatory curricular components, with emphasis on the subject of Historical and Theoretical-Methodological Foundations of Social Work. The research allowed us to verify that the PPCs of those mentioned components are aligned with the ABEPSS curricular guidelines and that, despite the efforts of UFAS to contemplate the contents proposed in the guidelines, the challenge of promoting the debate on the fundamentals through the articulation of the contents of the center’s basis of the guidelines is permanent.